Juridical Review of Legal Protection for Teachers in Carrying out Obligations to Discipline Students - Iswathoni, Juniar; Cahyowati, RR.; Kafrawi, Rachman Maulana (Faculty of Law, University of Dr. Soetomo, 2025)
The rise of various cases against teachers in carrying out their professional duties is proof that the legal protection of the teaching profession has not been running properly or as it should be. This study aims to understand, explain, and analyze the legal protection for teachers in carrying out their duties to discipline students. This research uses a normative legal research method. This study concludes that legal protection for teachers is one of the efforts to fulfill their rights, as mandated in Law No. 14 of 2005 on Teachers and Lecturers, Article 14. In the administration of education, the government has essentially made efforts to provide legal protection for teachers and other education personnel. However, these efforts are sometimes still inadequate and weak in their implementation. Teachers must perform their duties according to human rights principles (HAM). Teachers can discipline students firmly while still respecting human rights values, creating a positive learning environment, and shaping students' character without violating their fundamental rights. Several laws, such as Law No. 39 of 1999 on Human Rights, and Article 28B, paragraph (2) of the 1945 Constitution of the Republic of Indonesia, regulate the protection of students from the national legal perspective. The number of cases affecting teachers while carrying out their professional duties indicates that legal protection for the teaching profession has not been well implemented or as it should be.